Legal Implications of the Peace Agreement for Inheritance Disputes Made Before a Notary in Kolaka Regency, Southeast Sulawesi Province - Irawan Hamid, Sony (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study analyzes the legal implications of inheritance settlement agreements in Kolaka Regency, Southeast Sulawesi Province, focusing on the position and role of Notaries and the legal force of the resulting settlement agreements. Inheritance disputes in Indonesia, especially among Muslim communities, have become a complex juridical-social phenomenon with more than 50,000 new cases recorded in the Religious Courts in 2023. This study uses an empirical juridical method with a qualitative approach through in-depth interviews with Notaries, advocates, and heirs who have resolved inheritance disputes through notarial settlement agreements. The theoretical basis of the study includes the Theory of Agreement and Freedom of Contract, the Theory of Legal Certainty, the Theory of Restorative Justice, and the principle of Sulh in Islamic Law. This study recommends strengthening the mediation competence of Notaries, improving regulations on the role of Notaries in Alternative Dispute Resolution (ADR), conducting massive outreach to the public, simplifying the post-peace administration process, and improving coordination between Notaries, Religious Courts, and related agencies to optimize the resolution of inheritance disputes in Indonesia.